Investigation on the mesopause energetics and its possible implications on the equatorial MLTI processes through coordinated daytime airglow and radar measurements - Pant, T.K.; Tiwari, D.; Vineeth, C.; Thampi, Smitha V.; Sridharan, S.; Devasia, C.V.; Sridharan, R.; Gurubaran, S.; Sekar, R. (My University, 2007)
[1] This paper investigates the simultaneous presence of a prominent planetary scale modulations of quasi 16-day period observed in the daytime mean mesopause temperature and in the phase velocity of Type I electrojet irregularities during January–March 2001 over Trivandrum (8.5°N, 76.5°E, 0.5°N diplat.). The temperature was estimated from the Multiwavelength Dayglow Photometer (MWDPM) measurements of OH (8–3) Meinel band dayglow emissions. The radar measured phase velocity of the irregularities is found not only exhibiting ∼8 and quasi 16-day modulations, but also exceeding the isothermal ion-acoustic threshold i.e. ∼360 m/s for Trivandrum. The modulation in the mesopause temperature is attributed to the presence of planetary wave of quasi 16-day periodicity. Further, it is proposed that the temperature modulations which cause composition changes in the mesopause and equatorial electrojet region manifest as changes in the phase velocity through fluctuations in ion-neutral collisions corroborating with St.-Maurice et al. (2003).
Keywords: Radar measurements; Equatorial electrojet; Mesopause energetics; Electrojet irregularities; EEJ irregularities; MLTI